2011
DOI: 10.12659/msm.881391
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty in advanced osteonecrosis: The short-term results by metal-on-metal hip resurfacing

Abstract: SummaryBackgroundCharacteristically, osteonecrosis affects younger patients who typically refer to the orthopedic surgeon for the first time in the third to fifth decades of life, in the late stages of the disease. Femoral metal-on-metal hip resurfacing is as an alternative to conventional total hip arthroplasty in treating osteoarthritis of the hip. Since there are already many reports regarding the successful outcome of resurfacing in advanced osteoarthritis, the purpose of this study was to analyze the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In the present study, patients who underwent THR and TKR was encountered more among female, this agree with Liu et al (2012) and Stark (2016) [32,33] . In the opposite direction, Madadi et al (2011) and Thomas, Barrett, Tupper, Dacenko-Grawe, and Holm (2014) found that most of their studied patients were male [34,35] . As regards educational level, the findings of the present study represented that, more than half of patients, were non-educated.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, patients who underwent THR and TKR was encountered more among female, this agree with Liu et al (2012) and Stark (2016) [32,33] . In the opposite direction, Madadi et al (2011) and Thomas, Barrett, Tupper, Dacenko-Grawe, and Holm (2014) found that most of their studied patients were male [34,35] . As regards educational level, the findings of the present study represented that, more than half of patients, were non-educated.…”
Section: Discussionmentioning
confidence: 93%
“…Steroid-induced ONFH can lead to the femoral head collapse and subsequent hip joint destroys, which will significantly affect the patients' activities [15][16][17]. For steroids could target on multi-system or organs, it is relatively difficult to systemically interpret the mechanism involved in steroid-induced ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with those obtained by Madadi, who reported that the mean postoperative HHS was 94. 9 Moreover, Mont et al 10 reported a mean preoperative score of 52. These values suggest the substantial disability, pain and reduced joint range of motion among patients.…”
Section: Discussionmentioning
confidence: 99%